An evaluation of the Opening Minds Scale for Health Care Providers - Daguman EI; Taylor J (American Psychological Association, 2025)
Health workers hold stigmatizing attitudes toward people with mental distress, and contact-based interventions have been developed to address these attitudes. However, measures used to evaluate interventions have mixed validity support, including measures developed with service user involvement. The present study intended to provide a psychometric examination of one such measure, the 15-item Opening Minds Scale for Health Care Providers (Kassam et al., 2012; Modgill et al., 2014). With 286 health worker participants from a paid academic survey platform, including 19 retest samples, the focus was on addressing methodological limitations of previous psychometric evaluations. Current data demonstrated mixed fit to the known correlated three-factor structure (standardized root-mean-square residual [SRMR] = .057, root-mean-square error of approximation [RMSEA] = .054, comparative fit index = .754, Tucker–Lewis fit index = .897) and poor fit with the unidimensional model (SRMR = .080, RMSEA = .084, comparative fit index = .418, Tucker–Lewis fit index = .755). Data fitting to the bifactor solution (a structure comprising a general factor and three lower order factors) was attempted but did not converge. Scores had strong internal consistency (ωt = .73–.86), very weak test–retest reliability (r = −.46 to .21), and weak to moderate albeit statistically significant support for the interrelationship between the factors (rs = .32–.55). There is some evidence to consider the 15-item Opening Minds Scale for Health Care Providers as a viable measure of stigmatizing attitudes. However, further robust and transparent evaluations are still needed to surface better validity support.